L’ermite et le virtuose - Denis Laborde (Ateliers d'Anthropologie)
This contribution is devoted to two pianists virtuoso of the second half of the XXe century: Glenn Gould (1932-1982) and Georges Cziffra (1921-1994). Glenn Gould lived as an ascetic in Ontario, giving up concerts, which he likened to bullfights, to devote himself to recording. Georges Cziffra withdrew to Senlis, near the chapel of St. Frambourg which he turned into his foundation after having built the famous Festival de La Chaise-Dieu and having devoted a virtuoso lifetime to these concert halls and television studios that welcomed him worldwide. These two artists incarnated two conflicting pianist figures: one, for whom music practice was "not a demonstration of the soloist’s virtues (virtuosity) nor a complacent exhibition of self practice" (Schneider, 1988: 40), embodied the figure of the hermit artist in tune with "music", the other, "the guy who can play the piano faster than all others" (Böhm, 1995: 88), embodied the worldly face of the virtuoso. Neither was unanimously beloved nor did they leave anyone indifferent. Thus at the two extreme of this rhetoric of virtuosity, two conflicting faces of pianistic asceticism were constructed: Gould, absorbed by technology; Cziffra, by technique.